Implementasi Fuzzy Logic Controller Pada Kendali Kecepatan Sepeda Bertenaga Angin - Angga Prasetia; Tresna Dewi; A Rahman (Indonesian Society of Applied Science (ISAS), 2020)
One alternative for environmentally friendly vehicles is wind-powered bikes. This vehicle can reduce air pollution and can be convenient in big cities. The proposed bike is equipped with a distance sensor to sense the safe proximity to nearby obstacles. If the obstacles are below a reasonable distance, the mounted buzzer is active as the warning. This bike uses the wind generated by the 8045 hp dc rotation. The pulse-width (PWM) modulation is used to control a dc engine rotational speed with a fixed value of 155 = low and 255 = high. Fuzzy Logic Controller is used to increasing system effectivity to processes the input from the proximity sensor. The sufficient distance between the bike and the obstacles ahead, right and left, is set to be 1 meter. The PID controller ensures that the dc motor rotations are smooth and steady to ensure that the PWM value is still positive. In order to maintain a stable state Kp = 60, Ki = 4.2, and Kd = 2.9 are set as the appropriate settings for the used PID constants.